PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN POP UP BOOK 3D TERHADAP NUMERASI SISWA KELAS VI SEKOLAH DASAR - Faizah, Mulayyinah Muthi'atul; Yustitia, Via; Hadi, Susilo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the fact that students' numeracy skills in Indonesia are still low. This is proven by the 2018 PISA Indonesia graph. So there are still many students who do not understand numeracy literacy. Therefore, currently the priority is improving students' literacy and numeracy skills. The aim of this research was to determine whether there was an influence of the problem based learning model assisted by the 3D Pop Up Book on the numeracy of class VI elementary school students. This research uses a quantitative approach in the form of a quasi experimental design which uses a posttest only control design research design. by using two classes, namely the experimental class and the control class. The population in this study was 50 students, the sample was 25 students, the research method used side random clusters. The data collection method in this research is a test. Using statistical analysis methods with a formulation that is in accordance with the research title, namely the Effect of the Problem Based Learning Model Assisted by 3D Pop Up Books on Numeracy in Class VI Elementary School. A posttest only control design was used, then the T-test used SPSS version 25. Based on the research results, the T-test showed a sig (2-tailed) or p-value of 0.000 0.05, which means less than 0.05. So it can be concluded that Ho is rejected and Hi is accepted. Thus, it can be concluded that there is an influence of the Problem Based Learning Model Assisted by 3D Pop Up Books on the Numeracy of VI Elementary School Students